Anti-platelet aggregation activities of different grades of Angelica sinensis and their therapeutic mechanisms in rats with blood deficiency: insights from metabolomics and lipidomics analyses - Shen, Xue; Wu, Yangyang; Chen, Ping; Bai, Yuwei; Liu, Yanan; Jiang, Yihan; Zhang, Yawen; Yang, Zhigang (Frontiers in Pharmacology, 2024)
In traditional Chinese medicine, the radix of Angelica sinensis (Oliv.) Diels (RAS) are mainly used to replenish and invigorate the blood circulation. This study investigated the anti-platelet aggregation activity in New Zealand rabbits and high-performance liquid chromatography data to determine the spectrum-effect relationship of different commercial grades of RAS. Plasma and urine metabolites were examined using ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry-based metabolomics to elucidate their mechanisms in blood deficiency (BD) rats. Plasma and spleen metabolites were examined using ultra-performance liquid chromatography plus Q-Exactive tandem mass spectrometry-based lipidomics to clarify the mechanisms of RAS in treating BD. The third grade of RAS showed the best activity in replenishing and invigorating blood in vitro and in vivo. Ferulic acid, ligustilide, senkyunolide I, uridine, and guanine are quality markers of anti-platelet aggregation activity. Based on the metabolomics, 19 potential biomarkers were screened from plasma, and 12 potential metabolites were detected in urine. In lipidomics analyses, 73 potential biomarkers were screened from plasma, and 112 potential biomarkers were screened from the spleen. RAS may restore lipid metabolism by regulating glycerophospholipid and sphingolipid metabolism disorders, the tricarboxylic acid cycle, amino acid metabolism to improve energy metabolism, and arachidonic acid metabolism to promote blood circulation. These results provide a deeper understanding of the effects of different grades of RAS and a scientific reference to establish grade standards and clinical use of RAS.